2020
DOI: 10.1186/s40834-020-00127-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of pregnancy intendedness and prenatal contraceptive counseling on postpartum contraceptive use

Abstract: Background The study was conducted to prospectively examine how pregnancy intendedness and prenatal provider counseling about postpartum contraceptive options are associated with lack of contraception use at 6 months post-birth (e.g., increased risk for a short interpregnancy interval). Methods Logistic regression models were used to examine risk for no postpartum contraception use among a sample of low-income and racially/ethnically diverse women recruited from two metropolitan perinatal clinics in Tulsa, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This is a largely undercharacterized but important group between 2 extremes of a pregnancy intention continuum. 36 As shown here and in several prior studies, 36 , 37 , 38 if given this option, 13% to 40% women would classify themselves into this category. On the other hand, pregnancy intention among women who were avoiding pregnancy was fairly stable, in agreement with a previous study 35 that found that women who reported never desiring a pregnancy had the most stable pregnancy intention (78% did not change) at 12-month reassessment, whereas 60% of those contemplating pregnancy within the next year changed their desire.…”
Section: Discussionsupporting
confidence: 64%
“…This is a largely undercharacterized but important group between 2 extremes of a pregnancy intention continuum. 36 As shown here and in several prior studies, 36 , 37 , 38 if given this option, 13% to 40% women would classify themselves into this category. On the other hand, pregnancy intention among women who were avoiding pregnancy was fairly stable, in agreement with a previous study 35 that found that women who reported never desiring a pregnancy had the most stable pregnancy intention (78% did not change) at 12-month reassessment, whereas 60% of those contemplating pregnancy within the next year changed their desire.…”
Section: Discussionsupporting
confidence: 64%
“…20 Shreffler et al researched 44 respondents of trimester III pregnant women who were given counseling on contraception. 21 The results showed that there were significant differences in increasing knowledge after counseling was given. Another study conducted by Oduyebo et al also showed the same results.…”
Section: Discussionmentioning
confidence: 97%
“…The majority were aged 20-34 years. [15][16][17][18][19][20][21][22][23] This is due to the possibility that the group with a higher age assumes that the fertility rate has decreased so that they do not need contraception. Other research shows that respondents who are> 30 years old prefer not to use contraception, and the level of contraceptive use decreases at higher ages.…”
Section: Original Aerticlementioning
confidence: 99%
“…The data were collected with a survey designed by researchers based on the literature [6,[9][10][11] and the CIQ. [13] Developed by Bennet and Rocca (2015) and confirmed by Suid and Pasinlioğlu (2021) in terms of reliability and validity in Turkish, CIQ consists of 15 items in total with a 4-Point Likert scale.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…In the study, only 28.2% of the control group and 31.6% of the intervention group used modern contraceptive methods. [ 10 ] In their study evaluating the role of antenatal contraceptive counseling, Shreffler et al [ 11 ] suggested that women who do not plan another pregnancy after birth should be informed about contraceptive methods but those who think about it need information and counseling on the risks of short interpregnancy intervals. In this regard, it is of great significance that healthcare professionals should provide effective counseling and efficient training on all the contraceptive methods so as to prevent unintended pregnancy, specify interpregnancy interval, and ensure a conscious use of contraceptive methods.…”
Section: Introductionmentioning
confidence: 99%